Correlation Between Nursing Care Quality and Patient Satisfaction Level in Rumah Sakit JIH Yogyakarta - Aan Devianto; Catur Budi Susilo; Lina Eka Wati (Journal of Health (JoH), 2016)
Background: Nursing care quality as an indicator for the quality of health care is one of the determining factors for health care institutions image. Nurse is the profession with the highest number, at the front line and closest to the suffering and illness of patients and families. One of the indicators of nursing care quality is whether the nurses give satisfying services to patients or not. Objective: The goal of this research is to find out correlation between nursing care quality and patient satisfaction level in Rumah Sakit JIH Yogyakarta. Methodology: The type of this research is descriptive analytic non experimental; which used cross sectional approach. The technique for collecting sample was proportionate stratified random sampling; with 100 outpatients in Rumah Sakit JIH Yogyakarta as the respondents. The collecting sample used questionnaire while the analyzing used Rank Spearman Correlation. Result: The results of this research are (1) nursing care quality in Rumah Sakit JIH Yogyakarta are 45% good and 54% good enough, (2) patient satisfaction level in Rumah Sakit JIH Yogyakarta are 87% moderate level and 12% high level. The result for Rank Spearman is r account of 0,440; and it has probability of 0,000 (0,000 < 0,05). Hence, there is correlation between nursing care quality and patient satisfaction level in Rumah Sakit JIH Yogyakarta with the result in moderate level. Conclusion: the correlation between nursing care quality with outpatient satisfaction level in Rumah Sakit JIH Yogyakarta is on moderate level.